The use of information technology time method analysis of artery oscillograms for the study of adaptive mechanisms of the organism - Vakulenko, D. V. (Journal of Education, Health and Sport, 2015)
Vakulenko D V. Применение информационной технологии временного метода анализа артериальных осциллограмм для изучения адаптационных механизмов организма = The use of information technology time method analysis of artery oscillograms for the study of adaptive mechanisms of the organism. Journal of Education, Health and Sport. 2015;5(9):621-632. ISSN 2391-8306. DOI10.5281/zenodo.31730 http://dx.doi.org/10.5281/zenodo.31730 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A621-632 https://pbn.nauka.gov.pl/works/640916 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Применение информационной технологии временного метода анализа артериальных осциллограмм для изучения адаптационных механизмов организма The use of information technology time method analysis of artery oscillograms for the study of adaptive mechanisms of the organism Д. В. Вакуленко D V Vakulenko Тернопольский государственный медицинский университет им. И.Я. Горбачевского “I.Ya. Horbachevsky Ternopil State Medical University” Summary The reaction vessel shoulder on the compression at rest and after exposure to varying factors makes it possible to assess the state of the neuro-endocrine regulation of the cardiovascular system by the level of functioning of the autonomic nervous system, the functional capacity of the heart, a reflex reaction of the cardiovascular system, the state channel peripheral vessels (tone , elasticity, permeability), the activity of emergency response mechanisms for compression (baroretseptorni, hemoretseptorni, reflex ischemia) and others. The results make it possible to improve information diagnostics of the cardiovascular system by analyzing arterial waveform, registered in the measurement of blood pressure using, time analysis in each patient. Keywords: information technology, time analysis of arterial oscilogram. Резюме Реакция сосудов плеча на компрессию в состоянии покоя и после воздействия разнохарактерных факторов дает возможность оценить состояние нервно-эндокринной регуляции деятельности сердечно-сосудистой системы, уровень функционирования вегетативной нервной системы, функциональную способность сердца, рефлекторную реакцию сердечно-сосудистой системы, состояние русла периферических сосудов (тонус , эластичность, проходимость), активность механизмов срочной реакции на компрессию (барорецепторной, хеморецепторного, рефлекс на ишемию) и др. Полученные результаты дают возможность повысить информативность диагностики состояния сердечно-сосудистой системы путем анализа артериальной осциллограммы, зарегистрированной в процессе измерения артериального давления с применением, временного анализа у каждого пациента. Ключевые слова: информационные технологии, временной анализ осциллограмм. Резюме Застосування інформаційної технології часового методу аналізу артеріальних осцилограм для вивчення адаптаційних механізмів організму. Реакція судин плеча на компресію у стані спокою та після впливу різнохарактерних факторів дає можливість оцінити стан нервово-ендокринної регуляції діяльності серцево-судинної системи, рівень функціонування вегетативної нервової системи, функціональну здатність серця, рефлекторну реакцію серцево-судинної системи, стан русла периферійних судин (тонус, еластичність, прохідність), активність механізмів термінової реакції на компресію (барорецепторні, хеморецепторні, рефлекс на ішемію) тощо. Отримані результати дають можливість підвищити інформативність діагностики стану серцево-судинної системи шляхом аналізу артеріальної осцилограми, зареєстрованої у процесі вимірювання артеріального тиску із застосуванням, часового аналізу у кожного пацієнта. Ключові слова : інформаційні технології, часовий аналіз осцилограм.